Heparin-releasing scaffold for stem cells: a differentiating device for vascular aims. (July 2010) - Spadaccio, Cristiano; Rainer, Alberto; Centola, Matteo; Trombetta, Marcella; Chello, Massimo; Lusini, Mario; Covino, Elvio; Toyoda, Yoshiya; Genovese, Jorge A
Aims: Current limitations of tissue-engineered vascular grafts include timing for the scaffold preparation, cell type, cell differentiation and growth inside the construct, and thrombogenicity of the final device. To surmount these shortcomings, we developed a heparin-releasing poly-L -lactide (PLLA) scaffold using the electrospinning technique, to guide the differentiation of human mesenchymal stem cells towards the endothelial phenotype and to deliver a useful drug in the management of the postimplantation period.Materials & methods: The heparin-releasing PLLA scaffold was produced by means of the electrospinning technique in a tubular shape. The scaffold was seeded with human mesenchymal stem cells and cultured for up to 1 week. Cell viability and cytotoxicity assays were performed, and cell differentiation was evaluated by immunofluorescence with confocal microscopy, cytofluorometry and western blotting. Heparin release was assayed by Azure A method and biological effectiveness of the drug was assessed by activated clotting time measurements.Results: The scaffold exhibited a morphology favorable to cell attachment. Heparin release showed an initial burst within the first 24 h, followed by a further sustained release profile. After 48 h of culturing, the construct demonstrated adequate engraftment and viability. Increased proliferation compared with the control scaffold in bare PLLA, suggested the induction of a favorable microenvironment. A shift towards CD31 positivity and modifications in cell morphology were observed in the heparin-releasing PLLA scaffold.Conclusion: By exploiting the biological effects of heparin, we developed an ad hoc differentiating device towards the endothelial phenotype for autologous stem cell seeding and, at the same time, we were able to facilitate and optimize the management of the construct once in clinical settings.